"Green to be seen" and "brown to keep down": Visibility moderates the effect of identity on pro-environmental behavior. (August 2017) - Brick, Cameron; Sherman, David K.; Kim, Heejung S.
Abstract: Social identities predict pro-environmental behavior, but the strength may depend on whether the behavior is visible to others. When an environmentalist considers a pro-environmental behavior such as carrying reusable grocery bags, being observed by others may motivate signaling the valued group membership and may increase behavior ("green to be seen"). When an anti-environmentalist considers a pro-environmental behavior that signals an unwanted social identity, being observed may lead to less behavior ("brown to keep down"). United States residents completed three correlational surveys (total N = 1126) of identity, visibility, and self-reported behavior frequency using the Recurring Pro-environmental Behavior Scale. Three multilevel studies revealed that environmentalist identity predicted pro-environmental behavior more strongly for high-visibility behaviors, controlling for confounds at the person level (attitudes, political identity) and the behavior level (difficulty, effectiveness). This research helps uncover the key social identities and contextual factors that lead individuals to embrace or reject pro-environmental behaviors. Highlights: Environmental identity more strongly predicts pro-environmental behaviors when the behaviors are visible to others. Puzzling environmental decisions can be partially explained by integrating social visibility and social identity. Behavior visibility is assessed from each individual's perspective and analyzed with a multilevel model. The Recurring Pro-environmental Behavior Scale is introduced.